2018
DOI: 10.1039/c8ra00402a
|View full text |Cite
|
Sign up to set email alerts
|

Protic ionic liquids with primary alkylamine-derived cations: the dominance of hydrogen bonding on observed physicochemical properties

Abstract: The dominance of hydrogen bonds (networking) over the physicochemical features of primary alkylamine-PILs based on an amide acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…One study showed that the proton transfer is more complete with primary amines compared to tertiary amines [25]. This is caused by the level of hydrogen bonding that can occur within an ionic liquid, which then impacts on the physicochemical properties of the IL [26].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that the proton transfer is more complete with primary amines compared to tertiary amines [25]. This is caused by the level of hydrogen bonding that can occur within an ionic liquid, which then impacts on the physicochemical properties of the IL [26].…”
Section: Introductionmentioning
confidence: 99%
“…46 An extensive hydrogen bonding network in primary alkylammonium-based PILs with bis(trifluoromethanesulfonyl)amide leads to lower thermal stability and lower ionicity compared to their secondary and tertiary analogues. 38 The trend in the thermal properties (such as melting and decomposition temperatures) for ethylammonium-based PILs with nitrate, hydrogen sulfate, and thiocyanate anions is the same as that for the hydrogen bonding strength. 29 The stronger bonding interactions make these PILs more viscous and lower the ion mobility.…”
Section: ■ Introductionmentioning
confidence: 88%
“…An increase in the alkyl chain length of the cation and the degree of branching weakened the interaction between the ions in the trifluoroacetate-containing PILs with dimethylethyl, triethyl, tributyl, and diisopropylethylammonium cations . Depending on the cation and anion, the hydrogen bonds in primary alkylammonium-based PILs differ from each other covering the full range from strong, short, and linear to weak, long, and bent types. ,, An extensive study of ethylammonium nitrate (one of the earliest PILs) was performed to understand its fundamental properties. , It was shown that hydrogen bonding between the ethylammonium cation and the nitrate anion leads to the formation of a three-dimensional network structure, akin to water. , The same holds for propyl- and butylammonium nitrate and their solutions in acetonitrile, isopropanol, and methanol . An extensive hydrogen bonding network in primary alkylammonium-based PILs with bis­(trifluoro­methanesulfonyl)­amide leads to lower thermal stability and lower ionicity compared to their secondary and tertiary analogues .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations